The Effect of Mental Toughness on Decision Making in West Java PPLP Gymnasts - Maranata Tarigan; Helmy Firmansyah; Tri Martini (Journal of Physical Education Health and Sport, 2026)
Gymnastics is a closed-skill sport that demands an extremely high level of movement precision, complex routines, and full concentration. In the context of elite competition, the ability to make quick and accurate decisions is often associated with the athletes' mental toughness when facing high pressure from judges and performance expectations. This study aimed to empirically examine the effect of mental toughness on decision-making skills in elite gymnasts. This research used a correlational quantitative approach. The subjects were the entire population of 11 athletes from the West Java Student Sports Education and Training Center (PPLP) for gymnastics, selected using the total sampling technique. Data were collected systematically using the standardized Sports Mental Toughness Questionnaire (SMTQ), which measures confidence, constancy, and control, alongside an adapted decision-making questionnaire by Leykin & DeRubeis. Descriptive statistical analysis revealed a homogeneous phenomenon, where the majority of athletes (72.7%) had uniform levels of mental toughness and decision-making skills in the medium category. Based on the Shapiro-Wilk normality prerequisite test, the data distribution was partially not normal. Therefore, hypothesis testing was carried out using Kendall's Tau-b non-parametric statistical analysis. The test results showed a correlation coefficient of -0.200 with a significance value (p-value) of 0.420 (p > 0.05). These results conclude that statistically, there is no significant effect of mental toughness on decision-making skills in West Java PPLP gymnasts. These in-depth findings indicate that in closed-skill sports such as gymnastics, elite-level athletes tend to have reached an established stage of movement automation. Therefore, the effectiveness of decision-making in the field is dominated more by technical maturity and internalized muscle memory repetition, rather than by independent fluctuations in psychological variables.